PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT(PHBS) TATANAN RUMAH TANGGA DI JORONG BATU BASA KECAMATAN PARIANGAN - Ida Suryati; Lilisa Murni; Rara Raih Impian (Stikes Syedza Saintika Padang, 2025)
The implementation of clean and healthy living behavior (PHBS) should have become a healthy living behavior of the community because since this program was launched in 2011, it has been socialized, education has been carried out by related agencies directly or through electronic media according to the guidelines. In reality, the implementation of clean and healthy living behavior is not in accordance with the guidelines and government achievement targets. This needs to be addressed properly so that the implementation of clean and healthy living behavior becomes a lifestyle according to health regulations. This study was conducted in Jorong Batu Basa, Pariangan District, Tanah Datar Regency in 2025. The population was 200 families and the sampling technique was total sampling, carried out using the survey method and data processing using the Percentage technique. The results of the study showed that public knowledge about clean and healthy living behavior was high 85% and 15% low, attitudes 57% positive and 43% negative and the implementation of clean and healthy living behavior 56% good and 43% not good. The failure to achieve the implementation of clean and healthy living behavior according to the target with an achievement percentage of 56% of the target of 80% is a study material for related parties to design a program to improve the implementation of clean and healthy living behavior through solving problems and obstacles found in the field related to the completeness of TPA (Final Waste Disposal Site) facilities, hand washing education for children and adults, the availability of healthy toilets and not defecating in the river, and not smoking in the house.